2020
DOI: 10.1111/adj.12772
|View full text |Cite
|
Sign up to set email alerts
|

The state of bariatric dental care in Australia: a silent disability crisis?

Abstract: In the absence of dental related guidelines available in Australia specific to obesity and minimal awareness of the clinical implications on local dental practice, bariatric dental care can be perceived as a 'silent disability crisis'. This opinion piece and brief clinical note aims to question and raise awareness amongst dental professionals surrounding the current limited availability of bariatric dental chairs, difficulties in access, the safety of dental care delivery and ethical considerations for the den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Women in all the cohorts who were overweight/obese were more likely to be non‐attenders, with the highest risk of non‐attendance in the bigger BMI categories. While obesity is generally associated with higher use of healthcare services, 34 barriers to dental treatment may include difficulties of physical access (e.g., difficulties getting in and out of the dental chair or maximum lifting weight of the dental chair 14,35 ), difficulties in receiving optimal care due to extra weight around the neck and mouth 13 or higher levels of dental anxiety 13 . Of note, there are currently no guidelines for dental care of obese patients in Australia, and the only bariatric dental chairs are located within the public dental health system 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Women in all the cohorts who were overweight/obese were more likely to be non‐attenders, with the highest risk of non‐attendance in the bigger BMI categories. While obesity is generally associated with higher use of healthcare services, 34 barriers to dental treatment may include difficulties of physical access (e.g., difficulties getting in and out of the dental chair or maximum lifting weight of the dental chair 14,35 ), difficulties in receiving optimal care due to extra weight around the neck and mouth 13 or higher levels of dental anxiety 13 . Of note, there are currently no guidelines for dental care of obese patients in Australia, and the only bariatric dental chairs are located within the public dental health system 14 …”
Section: Discussionmentioning
confidence: 99%
“…13 Of note, there are currently no guidelines for dental care of obese patients in Australia, and the only bariatric dental chairs are located within the public dental health system. 14 Strengths of this study were the use of multiple waves of data, large community-based sample, the use of health-related variables with at least four levels (reflecting increasing intensity), and that the survey questions used to measure the variables of interest were repeated across the waves and were the same for all three cohorts, strengthening the credibility of our comparisons. The analysis was adjusted for a range of sociodemographic variables to take into account the different socioeconomic contexts of each cohort.…”
Section: Ta B L E 3 (Continued)mentioning
confidence: 93%
See 1 more Smart Citation
“…These negative associations worsen with increasing body mass index (BMI) 3 and, in addition to obesity‐related comorbidities, often complicate dental management 4,5 . As such, patients with clinically severe obesity may be considered for referral to dental specialists in Special Needs Dentistry for comprehensive dental management and appropriate modifications to their dental treatment plan including the use of bariatric dental chairs 6–8 …”
Section: Introductionmentioning
confidence: 99%
“…4,5 As such, patients with clinically severe obesity may be considered for referral to dental specialists in Special Needs Dentistry for comprehensive dental management and appropriate modifications to their dental treatment plan including the use of bariatric dental chairs. [6][7][8] Those attending a public hospital-based obesity service with clinically severe obesity tend to have higher rates of adverse diet and physical activity behaviours, and chronic diseases. 9,10 It has been consistently shown that obesity can also negatively impact upon important aspects of health-related quality of life (HRQoL), especially in the domains of physical health, emotional wellbeing, and psychosocial functioning.…”
Section: Introductionmentioning
confidence: 99%